Pengaruh Waktu Aplikasi Pupuk NPK Mutiara Terhadap Pertumbuhan dan Produksi Jagung Ketan (Zea mays ceratina L.) - Rismayani Rismayani; Novilda Elizabeth Mustamu; Kamsia Dorliana Sitanggang; Badrul Ainy Dalimunthe (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
Sticky corn varieties (waxy corn) are local varieties of corn. Pulut corn is developed in several areas of South Sulawesi. It has the advantage that it tastes delicious and savory so it can be used as a food ingredient. This study aims to determine the growth and yield of glutinous corn ( Zea mays ceratina L.) from different application times. This research was conducted in an experimental field in Tebing Linggahara Village, Bilahbarat District, Labuhanbatu Regency, North Sumatra. This research was conducted from April to June 2021. The design used in this study was a Non-Faculty Randomized Block Design (RAK).torial with 6 levels of treatment. Based on the research that has been done, it can be concluded that: treatment time of NPK Mutiara fertilizer application did not significantly affect plant height and number of leaves. And gave a significant effect on the age of flowering, weight of the cob and the number of rows/seeds. Keywords: NPK Mutiara , growth, production, glutinous corn